United States Adults Meeting 2010 American College of Rheumatology Criteria for Treatment and Prevention of Glucocorticoid‐Induced Osteoporosis. Issue 11 (November 2014) - Overman, Robert A.; Toliver, Joshua C.; Yeh, Jun‐Yen; Gourlay, Margaret L.; Deal, Chad L.
<x xml:space="preserve">Abstract</x> Objective The American College of Rheumatology (ACR) updated its guidelines on the prevention and treatment of glucocorticoid‐induced osteoporosis (GIO) in 2010. An unknown proportion of US adults at risk of fracture due to glucocorticoid use would be recommended antiosteoporosis pharmaceutical (AOP) therapies based on the ACR guidelines. Methods Using the 2005–2010 National Health and Nutrition Examination Survey (NHANES) data for postmenopausal women (PMW), and men age ≥50 years reporting current glucocorticoid use, we categorized individuals according to ACR criteria for low, medium, and high fracture risk (<10%, ≥10%, and ≥20%, respectively) and provided percentages of treatment recommendations for chronic (≥90 days) medium and all high‐risk patients. Results Glucocorticoids were used by 1.66% of PMW and 1.65% of men age ≥50 years. Of these patients, 0.80% of PMW and 0.45% of men age ≥50 years were at high risk of fracture. A majority of PMW (81.2%) and men age ≥50 years (75.8%) were chronic glucocorticoid users. In patients for whom treatment recommendations could be made, 64.9% of PMW and 51.9% of men age ≥50 years would be recommended therapy, but only 28.4% of PMW and 9.7% of men age ≥50 years reported AOP use. Conclusion Based on the NHANES (2005–2010) data, we estimate glucocorticoid use in >1.5 million US PMW and men age ≥50 years. Treatment would be recommended in at least 50% of this population based on the 2010 ACR guidelines. Self‐reported AOP use was documented in <30%, suggesting a treatment gap in the management of GIO in the US before the guideline release.